미국 농정의 변화와 도전 - Daniel A. Sumner (한국농촌경제연구원, 2008)
This report provides background on agricultural policy in the United States in order to place potential change in context. It focuses on both the short run prospects for the Farm Bill that is likely to be finalized soon and for longer changes in U.S. policy. Because federal policies are the ones that matter nationally and internationally, they are the focus on this report. Furthermore, all significant agricultural policy is under the purview of the United States Department of Agriculture (USDA) and especially the Farm Service Agency (FSA). The National Resource Conservation Service (NRCS) operate some environmental programs, such as the Environmental Quality Improvement Program (EQIP). Food subsidies and rural development programs are operated by other USDA agencies. Farm Bills typically include many separate titles and deal with food and nutrition subsidies, environmental subsidies, international food aid, rural development assistance, research and well as farm subsidies. Legislation must be passed by Congress and the administration often has a limited role in determining the content of the major farm policies. (For example, in 2008 the Farm Bill easily passed over the veto of President Bush.) Congressional committees work closely with representatives from major farm organizations, environmental groups and other advocated to shape legislation that will pass both the House and the Senate. University economists as well as the USDA often provides analysis used in determining the likely budget and other effects of potential legislation. Policy implementation is typically the role of the USDA. USDA has several branch offices in every state. These include offices of the Farm Service Agency (FSA), the Risk Management Agency (RMS), the Natural Resources and Conservation Service (NRCS), among others dealing with rural development and food and assistance. Agricultural R&D policy for agriculture is a joint state and federal responsibility. The federal government funds the Agricultural Research Service (ARS), which has research stations and researchers co-located at universities. The federal government also supports research at universities and other organizations through formula funds transferred to states and through competitive grants administered by the CSREES. Issues for policy change include the skewed distribution of benefits across commodities and regions, conflict with international obligations, budget and market opportunities and the general lack of convincing public rationale for the current programs. However, none of these issues affected the final outcome in 2008. Farm programs have continued from about 75 years and 2008 was a continuation of the long history. After some important changes in the 1990s policy change stalled or reversed in 2002 and 2008. The many rationales suggested for commodity programs are easily shown to either not apply currently or to be based on empirical or logical errors. For example, the current programs do little to aid risk management and if that were a serious objective of farm programs there is no rationale to limit their extent to a handful of crops covering less than half of all U.S. farm production value. Furthermore, farmers are relatively wealthy people in the United States and the farm program benefits are targeted towards the relatively wealthy among the farmers. The strongest rationale for farm programs is that they have continued for so long that many farmers and landowners cannot imagine how their industries would operate in absence of farm subsidy programs. It is extremely difficult to generalize from one set of national conditions to another. However, it may be useful to mentions a few lessons from U.S. agricultural policy that could be applicable to Korea as Korean agricultural completes its transition to a part of a relatively wealthy society where agriculture’s share of employment and economic output is very small. U.S. agricultural policy was developed to subsidize farm operators and landowners at a time when farm prices were very low and the whole world economy was in a terrible depression. Because farm size has grown steadily and numbers of full time farm operators who make most of their income from farming is now very small, U.S. agricultural policy does not face the issue of how to provide a retirement income for large numbers of relatively low-income farmers. The lessons from the United States, however, is that support for commodities does not do much for long term incomes of farm people. Finally, one of the successes of U.S. agricultural policy has been funding for agricultural R&D. This funding has included both state and federal governments. Korea also has substantial agricultural R&D and a well-established process for funding and operation of R&D projects (Choi, Lee and Sumner). More funding for this effort and perhaps more flexibility to examine a broad range of crops and issues would likely be useful.